Postinfectious T-lymphocytic enteral leiomyositis as a rare cause of chronic intestinal pseudoobstruction - Sarfo, Bismark Osei; Kopdag, Hakan; Pott, Marian-Christopher; Stiedenroth, Lars; Nahrstedt, Ulf; Schäfer, Hansjörg; von Wichert, Götz (Zeitschrift für Gastroenterologie, 2021)
T-lymphocytic enteral leiomyositis (T-lel) is a rare disorder causing chronic intestinal pseudo-obstruction (CIPO), with cases predominantly being reported in the field of veterinary and pediatric medicine. Here, we present a case of T-lel-associated CIPO in an adult female, who initially presented with a paralytic ileus 2 weeks after a common gastroenteritis. The histological diagnosis was established through full-thickness bowel biopsy, exhibiting a dense lymphocytic infiltrate in the lamina muscularis of the intestinal wall. This case shows that T-lel can be a cause of chronic intestinal pseudo-obstruction not only in children but also in adults. A subsequent induction of an immunosuppressive therapy with steroids, azathioprine, and ultimately TNF-alpha-inhibiting antibodies led to a slow recovery and stable disease.
Keywords: gastrointestinal motility; malassimilation; infectious colitis